2020
DOI: 10.1155/2020/6152041
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Large-Scale Wearable Device Data for Predicting the Epidemic Trend of COVID-19

Abstract: The pandemics of COVID-19 triggered out an alarm on the public health surveillance. The popularity of wearable devices enables a new perspective for the precaution of the infectious diseases. In this study, we propose a framework, which is based on the heart rate and sleep data collected from the wearable devices, to predict the epidemic trend of COVID-19 in different countries and cities. On top of a physiological anomaly detection algorithm defined based on wearable device data, an online neural network pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 27 publications
1
58
0
Order By: Relevance
“…This work builds on our earlier retrospective analysis demonstrating the potential for consumer sensors to identify individuals with influenza-like illness, which has subsequently been replicated in a similar analysis of over 1.3 million wearable users in China for predicting COVID-19 8,9 . In response to the COVID-19 pandemic, a number of prospective studies, led by device manufacturers and/or academic institutions, including DETECT, have accelerated deployment to allow interested individuals to voluntarily share their sensor and clinical data to help address the global crisis [10][11][12][13][14] .…”
Section: Discussionmentioning
confidence: 87%
“…This work builds on our earlier retrospective analysis demonstrating the potential for consumer sensors to identify individuals with influenza-like illness, which has subsequently been replicated in a similar analysis of over 1.3 million wearable users in China for predicting COVID-19 8,9 . In response to the COVID-19 pandemic, a number of prospective studies, led by device manufacturers and/or academic institutions, including DETECT, have accelerated deployment to allow interested individuals to voluntarily share their sensor and clinical data to help address the global crisis [10][11][12][13][14] .…”
Section: Discussionmentioning
confidence: 87%
“…Wearable sensors have also been used to detect atrial fibrillation 6 . Other recent studies have shown that elevated heart rate measurements from smartwatches can be used in epidemiological studies to track the spread of respiratory viruses 7,8 .…”
mentioning
confidence: 99%
“…Wearable devices: In [400] , a framework is proposed that collects data about heart rate and sleep data collected from wearable devices to predict the pandemic trend. In this approach, an online neural network algorithm is proposed to build the required model.…”
Section: Applications Of Ai In Epidemiologymentioning
confidence: 99%